The dentin phosphoprotein repeat region and inherited defects of dentin. - Yang, Jie; Kawasaki, Kazuhiko; Lee, Moses; Reid, Bryan M; Nunez, Stephanie M; Choi, Murim; Seymen, Figen; Koruyucu, Mine; Kasimoglu, Yelda; Estrella-Yuson, Ninna; Lin, Brent P J; Simmer, James P; et al. (Mol Genet Genomic Med, 2016)
Nonsyndromic dentin defects classified as type II dentin dysplasia and types II and III dentinogenesis imperfecta are caused by mutations in DSPP (dentin sialophosphoprotein). Most reported disease-causing DSPP mutations occur within the repetitive DPP (dentin phosphoprotein) coding sequence. We characterized the DPP sequences of five probands with inherited dentin defects using single molecule real-time (SMRT) DNA sequencing. Eight of the 10 sequences matched previously reported DPP length haplotypes and two were novel. Alignment with known DPP sequences showed 32 indels arranged in 36 different patterns. Sixteen of the 32 indels were not represented in more than one haplotype. The 25 haplotypes with confirmed indels were aligned to generate a tree that describes how the length variations might have evolved. Some indels were independently generated in multiple lines. A previously reported disease-causing DSPP mutation in Family 1 was confirmed and its position clarified (c.3135delC; p.Ser1045Argfs*269). A novel frameshift mutation (c.3504_3508dup; p.Asp1170Alafs*146) caused the dentin defects in Family 2. A COL1A2 (c.2027G>A or p.Gly676Asp) missense mutation, discovered by whole-exome sequencing, caused the dentin defects in Family 3. We conclude that SMRT sequencing characterizes the DPP repeat region without cloning and can improve our understanding of normal and pathological length variations in DSPP alleles.

Root anomalies and dentin dysplasia in autosomal recessive hyperphosphatemic familial tumoral calcinosis (HFTC). - Vieira, Alexandre R; Lee, Moses; Vairo, Filippo; Loguercio Leite, Julio Cesar; Munerato, Maria Cristina; Visioli, Fernanda; D'Ávila, Stéphanie Rodrigues; Wang, Shih-Kai; Choi, Murim; Simmer, James P; Hu, Jan C-C (Oral Surg Oral Med Oral Pathol Oral Radiol, 2015)
Hyperphosphatemic familial tumoral calcinosis (HFTC, OMIM #211900) is an autosomal recessive metabolic disorder characterized by hyperphosphatemia, tooth root defects, and the progressive deposition of calcium phosphate crystals in periarticular spaces, soft tissues, and sometimes bone.(1) In this HFTC case report, we document the dental phenotype associated with a homozygous missense mutation (g.29077 C>T; c.484 C>T; p.Arg162*) in GALNT3 (OMIM 6017563), a gene encoding UDP-GalNAc transferase 3 that catalyzes the first step of O-linked oligosaccharide biosynthesis in the Golgi. The medical and dental pathology is believed to be caused primarily by high serum phosphate levels (hyperphosphatemia), which, in turn, is caused by failure of GALNT3 to glycosylate the phosphate regulator protein FGF23, impairing its ability inhibit reabsorption of filtered phosphate in the kidneys.
Keywords: Adolescent; Calcinosis; Dentin Dysplasia; Humans; Hyperostosis, Cortical, Congenital; Hyperphosphatemia; Male; Mutation, Missense; N-Acetylgalactosaminyltransferases; Pedigree; Phenotype; Radiography, Panoramic; Tooth Root